2010
DOI: 10.1007/s00192-009-1080-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing long-term pessary use

Abstract: Age greater than 72 years was associated with continued pessary use and history of hysterectomy or prolapse surgery, and stress incontinence were associated with discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Pessaries have few complications, although some authors suggest that they require lifestyle modification, 13,14 and the variety of shapes and sizes available affords choice and individual fitting. 15 However, data on complications relevant to appropriate discussion of consent with patients and planning of long-term follow up strategies are limited. The side effects of pessary use are not obvious; moreover it is not clear whether the therapeutic impact is high enough to overlook possible risks or which patients benefit the most from pessary treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Pessaries have few complications, although some authors suggest that they require lifestyle modification, 13,14 and the variety of shapes and sizes available affords choice and individual fitting. 15 However, data on complications relevant to appropriate discussion of consent with patients and planning of long-term follow up strategies are limited. The side effects of pessary use are not obvious; moreover it is not clear whether the therapeutic impact is high enough to overlook possible risks or which patients benefit the most from pessary treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is unfortunate that publication delay may have prevented Friedman et al [1] from citing our recent article [2]. We showed that in six patients with complete uterine prolapse who were fitted with ring pessary, prolapse disappeared even after pessary removal.…”
mentioning
confidence: 73%
“…Longterm follow-up was needed to clarify this phenomenon. The importance of long-term follow-up was also described by Friedman et al [1].…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Pessaries can be successfully fitted in most women [49], with observational studies reporting success in around 50-100 % of cases; however, successful continuation of pessary therapy is much lower, with a reported rate of 14-67% [50][51][52][53][54][55][56][57][58][59]. In addition to prolapse symptoms, stress incontinence has been reported to improve in 23-45 % of cases; studies have also reported improvements for overactive bladder, defecation disorders, sexual function and body image [52,[60][61][62][63].…”
Section: Pessary Therapymentioning
confidence: 99%